Pengaruh Kepedulian Lingkungan dan Persepsi Kontrol Perilaku terhadap Niat pembelian Mobil Listrik dengan Sikap, Norma Subjektif, dan Norma Moral sebagai Variabel Mediasi - Eriskha Fridenia Maharani; Tanding Suryandari, Retno (JURNAL MANAJEMEN MOTIVASI, 2026)
This study examines the influence of environmental concern and perceived behavioral control on electric vehicle purchase intention, with attitude, subjective norm, and moral norm as mediating variables. The research aims to analyze the direct and indirect effects of these factors on consumers’ intention to purchase electric vehicles in Surakarta. Using a quantitative approach, data are collected through a survey and analyzed using Structural Equation Modeling (SEM). The findings are expected to demonstrate the significant role of environmental concern and perceived behavioral control in shaping purchase intention through psychological and social mechanisms. The study provides implications for policymakers and automotive industries in promoting sustainable transportation. Keywords: Environmental Concern; Perceived Behavioral Control; Attitude; Subjective Norm; Moral Norm; Electric Vehicle Purchase Intention; Theory of Planned Behavior; Sustainable Transportation.